The Role of Islamic Macroeconomics and Islamic Finance in Driving Islamic Economic Growth - Mutmainah; Romadhon, Muhammad Ryan (Universitas Airlangga, 2025)
A country's economic growth is closely related to world economic conditions. Global macroeconomic analysis is measured from 3 indicators, namely the increase in gross domestic product, the level of world trade, and the global inflation rate. The indicators to analyze Islamic economic conditions globally can be seen from the real sector and the financial sector. This research will synthesize into a study that aims to analyze the influence of Islamic macroeconomics and finance on Indonesia's sharia economic growth. By using quarterly time series data in Indonesia for 5 years from 2019 to 2023 and using ECM (Error Correction Model) analysis as a regression model and assisted by the Eviews analysis tool to analyze research data. Research findings reveal that in the short term inflation and Islamic finance have no effect on economic growth, while export and import variables affect economic growth. On the other hand, in the long run exports, imports and Islamic finance affect economic growth while inflation variables do not affect economic growth.